Apie sujungiamųjų žodžių junginių klasifikaciją - Kaukėnienė, Lidija (Respectus Philologicus, 1999)
The subject of this study is word combinations. Some linguists describe coordinating word combinations as word combinations while others disagree with this classification. A discussion of contemporary Lithuanian grammar must address this issue, since it is very difficult to distribute compound coordinating word combinations. Such combinations can be divided into two parts: simple and compound; compound word combinations may be further characterized by complicated coordination. There are two methods of coordination, with conjunctions and without, and there are two types of compound coordinating word combinations, symmetrical and asymmetrical. Compound coordinating word combinations generally have two components, though they may also have one, three, five or even more members. In the majority of cases asymmetrical word combinations are made up of two components, the first of which containing one member and the second two or three members.